Analisis Strategi Pemasaran Digital Layanan Indibiz dalam Menjangkau Usaha Kecil dan Menengah di Kota Yogyakarta - W.M. Rhomas Nabbaro AS; Albari Albari (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
This study aims to determine the effectiveness of the Indibiz service marketing strategy implemented by PT Telkom Indonesia Witel Yogyakarta in reaching Small and Medium Enterprises (SMEs). The background of this study is based on the low level of awareness and utilization of Indibiz B2B digital services among SMEs, even though the product is designed to support digital business transformation. This study uses a qualitative descriptive approach with a case study method. Data were collected through in-depth interviews, observations, and documentation involving Indibiz Account Managers and SME customers in Yogyakarta City. The results show that the implementation of the 7P marketing mix and digital marketing strategies have a positive effect on increasing brand awareness, satisfaction, and customer loyalty. Product, process, and people elements are the dominant factors that shape customer satisfaction, while digital promotion and price aspects still need to be improved. A personal approach through Account Managers has proven effective in building long-term relationships with customers. This study provides an empirical contribution to the B2B service marketing literature, with an emphasis on the importance of educational communication and interpersonal relationships in digital marketing strategies. These findings also offer practical implications for Telkom Indonesia to strengthen education-based promotional strategies and develop customer loyalty programs in the SME segment.